An X-ray characterization of the central region of the supernova remnant G332.5-5.6 - Suárez, Alejandra E. (2015)
Fil: Suárez, Alejandra E. Universidad Nacional de la Plata. Facultad de Ciencias Astronómicas y Geofísicas; Argentina